Bats of Mount Penrisen, Padawan, Sarawak - Kumaran, Jayaraj Vijaya; Anwarali, F. A.; Abdullah, M.T (Universiti Malaysia Sarawak, (UNIMAS), 2014)
We surveyed bats near the Hornbill Golf and Jungle Club Resort in the highland area of Mount Penrissen from 27 to 29 January 2005. We caught 38 individuals of 8 species in ten mist-nets and one harp-trap during two trapping nights. These represent new distributional records forMount Penrisen (Payne et al., 1998).